1985
DOI: 10.1212/wnl.35.2.244
|View full text |Cite
|
Sign up to set email alerts
|

Positron emission tomography in the newborn

Abstract: Regional cerebral blood flow (CBF) was measured by positron emission tomography (PET) with 15O-labeled water in an asphyxiated infant during a seizure. After intrauterine asphyxia, the infant had a syndrome characteristic of hypoxic-ischemic encephalopathy. During a PET scan on the second postnatal day, the infant had a focal seizure with deviation of eyes to the right and clonic jerking of the right arm. Regional blood flow was highest, about 80 ml/100 g/min, in the left temporal-parietal frontal region of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1986
1986
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…CBF-metabolism coupling is probably developed in the preterm infants by 32 wk of gestation, if not earlier (67). Excessive neuronal activity during seizures has been associated with increased CBF and CBF velocity in term newborn and preterm infants, respectively (23,150). Changes in the regional distribution of CBF during infancy and childhood correlate with changes in the local pattern of glucose utilization in the brain (35), supporting the concept of CBF-metabolism coupling in the developing brain.…”
Section: Cerebral Blood Flow-metabolism Coupling In the Pre-mentioning
confidence: 74%
“…CBF-metabolism coupling is probably developed in the preterm infants by 32 wk of gestation, if not earlier (67). Excessive neuronal activity during seizures has been associated with increased CBF and CBF velocity in term newborn and preterm infants, respectively (23,150). Changes in the regional distribution of CBF during infancy and childhood correlate with changes in the local pattern of glucose utilization in the brain (35), supporting the concept of CBF-metabolism coupling in the developing brain.…”
Section: Cerebral Blood Flow-metabolism Coupling In the Pre-mentioning
confidence: 74%
“…The arterial hypertension and increased CBF associated with seizure activity in the adult are also seen in many experimental models of neonatal seizures, and possibly in humans (Monin et al, 1990;Wagerle and Delivoria-Papdopoulos, 1990). Increases in local CBF were obseked during focal penicillin seizures in newborn macaque monkeys (Hosokawa et al, 1977), generalized seizures in newborn dogs (Young et al, 1985) and piglets (Clozel et al, 1985;Park et al, 1987;Monin et al, 1990), and were observed by positron emission tomography (PET) in an asphyxiated human infant during a focal motor seizure (Perlman et al, 1985). On the other hand, studies of bicuculline-induced seizures in newborn marmoset monkeys showed large increases in brainstem blood flow but little or no increase in forebrain structures .…”
Section: Cerebral Blood Flow and Metabolism In Neonatal Sementioning
confidence: 99%
“…Studies with radiolabelled water suggest that after intraventricular haemorrhage there is marked impairment of regional cerebral blood flow in the hemisphere containing an apparently restricted intracerebral haematoma [8]. Furthermore, parasagittal cerebral blood flow is disturbed in asphyxiated term infants [9], and the flow increases in the hemisphere opposite to the lesion during a one-sided focal seizure [10].…”
Section: Introductionmentioning
confidence: 99%